Diane Tillman’s Concept in Instilling the Values of Religious Moderation at SMP Negeri 1 Sanggau - Nabila, Munadhil; Supriyatno, Triyo; Maimun, Agus (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This study investigates the implementation of religious moderation in a multicultural school context, focusing on how SMP Negeri 1 Sanggau integrates these values into its educational environment. Motivated by the growing need to cultivate inclusive and tolerant attitudes among students, the research aims to explore the application of religious moderation values and examine institutional efforts to internalize these principles in daily school life. Employing a qualitative case study design, participants were selected through purposive sampling and included Islamic Religious Education teachers, school administrators, homeroom teachers, and student representatives. Data were collected through direct observation of both curricular and extracurricular activities, unstructured interviews, and analysis of the school’s social media content. The findings reveal that the school promotes religious moderation through a universal values-based approach, specifically drawing from Diane Tillman’s Living Values Education (LVE) framework. Core values such as tolerance, peace, cooperation, and unity are not only incorporated into classroom instruction but are also embedded in school-wide practices, including interfaith celebrations, local wisdom projects, and the routine cultivation of inclusive attitudes. The study concludes that the integration of universal character values provides an effective foundation for fostering religious moderation without privileging any particular religious identity. This approach offers practical implications for the development of character education models in multicultural educational settings.